Structure Design and Bearing Capacity Analysis for Crawler Chassis of Rice Combine Harvester. (4th May 2020) - Tang, Zhong; Ren, Hui; Li, Xiyao; Liu, Xin; Zhang, Biao
Abstract : Due to the current unstable travel performance and poor driving maneuverability of rice combine harvester crawler chassis with high load in the rice field, the driver's standard sitting posture model was developed by analyzing the handling of the crawler chassis driving control panel. Based on this model, the joystick length and cab manipulation space layout were designed. The Finite Element Software was used to develop the loading and restraining model of the chassis frame, and then the structural characteristics and bearing capacity of the crawler chassis were analyzed. The high-bearing running stability and the rationality of operating force of the joystick of rice combine harvester crawler chassis designed in this paper through experiments were verified by experiments. The results showed that when the crawler chassis of rice combine harvester bears a load of 3.5 t, the driving speed is relatively stable in the three speed ranges of 1 m/s, 1.5 m/s, and 2 m/s, and the maximum variance of driving speed variation is 5.022 × 10 −4 . The actual average operating force of each operating lever on the crawler chassis ranges from 30.36 to 42.71 N, and the operating force of each operating lever is suitable for 95% of Chinese adult male operators. The research results provide a good method and reference for the future development of the crawler chassis structure of rice combine harvester.